DAMPAK INFLUENCER DI MEDIA SOSIAL TERHADAP MORAL GENEREASI ALPHA - Mawaddah, Tsaltsah; Maulida, Utami (Elementar : Jurnal Pendidikan Dasar, 2024)
This research uses a descriptive qualitative approach. To comprehensively examine the new lifestyle among alpha generation students which is the impact of influencers on social media. The results of this research show that influencers on social media have had positive and negative impacts on the morale of MI Almabruroh Tangerang students. Efforts to minimize the negative impact of influencers on social media on student morale at MI Almabruroh Tangerang can be done in five ways, namely limiting students' time using social media, controlling and filtering influencer content on social media, providing education on the good and bad impacts of social media, increasing activities. extracurricular activities and providing counseling guidance at school. The positive impact of influencers on social media on student morale is that it can foster a sense of social awareness, increase a sense of empathy, and train students' independence. The negative impact is the degradation of language, the loss of feelings of shame and the erosion of students' respect.